Neuroprotective Potential of Tamarillo (Cyphomandra betacea) Epicarp Extracts Obtained by Sustainable Extraction Process - Suárez-Montenegro, Zully Jimena; Ballesteros-Vivas, Diego; Gallego, Rocío; Valdés, Alberto; Sánchez-Martínez, Jose David; Parada-Alfonso, Fabián; Ibáñez, Elena; Cifuentes, Alejandro (Frontiers in Nutrition, 2021)
Tamarillo (Cyphomandra betacea (Cav.) Sendt.) or tree tomato, is a tropical fruit from the Andean region of South America; it is highly rich in vitamins, minerals and polyphenolic compounds. In this work, extracts from tamarillo epicarp (TE) were obtained by pressurized liquid extraction (PLE), and their in-vitro neuroprotective potential was assessed. A central composite design with response surface methodology was performed to optimize PLE as a function of solvent composition and temperature. Selected response variables were extraction yield, total phenolic content (TPC), total flavonoid content (TFC), total carotenoid content (TCC), antioxidant (ABTS) and anti-inflammatory (LOX) activities and anti-acetylcholinesterase (AChE) inhibitory capacity. According to the desirability function, the optimal conditions were 100% ethanol and 180 °C with a 0.87 desirability value. Next, the anti-butyrylcholinesterase enzyme (BChE), reactive oxygen (ROS) and nitrogen (RNS) species inhibition as well as cytotoxicity in human HK-2, THP-1 monocytes and SH-5YSY neuroblastoma cells lines were studied for the TE extract obtained under the optimized conditions. The optimum TE extract provided the following results: extraction yield (36.25%), TPC (92.09 mg GAE/g extract), TFC (4.40 mg QE/g extract), TCC (107.15 mg CE/g extract), antioxidant capacity (ABTS, IC50= 6.33 mg/mL extract), LOX (IC50= 48.30 mg/mL extract) and AChE (IC50= 97.46 mg/mL extract), and showed no toxicity at concentration up to 120 µg/mL extract for all the tested cell lines. Finally, chemical characterization by liquid chromatography-tandem mass spectrometry (UHPLC-q-TOF-MS/MS) of the optimum TE extract exhibited an important presence of hydroxycinnamic acid derivatives and other phenolic acids as well as quercetin hexoside and rutin, as main metabolites responsible of the observed biological properties. All these results suggested that TE -which represent between 8-15% of the total fruit- could become a promissory natural by-product with a potential “multitarget” activity against Alzheimer disease.